New theorems on extended b-metric spaces under new contractions - Mukheimer, Aiman; Mlaiki, Nabil; Abodayeh, Kamal; Shatanawi, Wasfi (Nonlinear Analysis: Modelling and Control, 2019)
The notion of extended b-metric space plays an important role in the field of applied analysis to construct new theorems in the field of fixed point theory. In this paper, we construct and prove new theorems in the filed of fixed point theorems under some new contractions. Our results extend and modify many existing results in the literature. Also, we provide an example to show the validity of our results. Moreover, we apply our result to solve the existence and uniqueness of such equations.
Keywords: fixed point; b-metric spaces; contraction